Molecular characterization of hemoglobinopathies and thalassemias in Northern Guangdong Province, China. Issue 45 (12th November 2021) - Ma, Zhanzhong; Fan, Shushu; Liu, Jun; Liu, Yulan; Guo, Yanle; Huang, Wenbo
Abstract : Abstract: To detect the molecular characterization of hemoglobinopathies and thalassemias in Northern Guangdong Province of China. We recruited 10, 285 subjects who were screened for hemoglobin (Hb) variants and thalassaemia genotypes in the outpatient department of Yuebei People's Hospital from January 2018 to December 2020. The subjects collected venous blood samples for blood cell parameter analysis and Hb electrophoresis analysis. When the average red blood cell volume is <82 fL, or the average red blood cell Hb is <27 pg, or HbA2 > 3.5%, or HbA2 < 2.5%, or HbF > 2.0%, the screening is positive if one of them is satisfied. All subjects who were screened positive were tested for the thalassaemia gene by gap-polymerase chain reaction, PCR-based reverse dot blot, and DNA sequencing. Among all subjects screened, the overall prevalence of hemoglobinopathies and thalassemias were 0.46% (47/10, 285) and 21.02% (2162/10, 285) in Northern Guangdong Province. We found that Hb Q-Thailand is the most common, and other types of hemoglobinopathies are followed by Hb E, Hb New York, Hb G-Chinese, Hb G-Coushatta, Hb J-Bangkok, Hb J-Broussais, Hb Ottawa, and Hb G-Taipei. We identified 1340 cases (13.03%) of α-thalassemia, mainly includes – SEA deletion (71.64%), –α 3.7 deletion (12.01%), –α 4.2 deletion (4.78%). And identified 652 cases (6.34%) of β-thalassemia, the most prevalent being CD 41/42(-TTCT) (35.89%), IVS-II-654 (C > T) (33.44%), CD 17 (A > T) (10.28%) and –28(A > G) (9.66%). Furthermore, there are 170 cases (1.65%) of α combined β thalassaemia. In addition, we found a rare case with –80 (T > A) of β-thalassemia. The results of this study found a high prevalence of hemoglobinopathies and thalassemias in Northern Guangdong Province, China. There were some differences molecular characterizations of thalassemia in different areas of China. Our results enriched the related information of hemoglobinopathies and thalassemias in the region, which provided valuable references for the prevention and control of thalassemia.